Role and mechanism of molecular hydrogen in the treatment of Parkinson’s diseases - Wang, Fengjiao; Zhang, Guangjie; Zhai, Qingfeng (Frontiers in Neuroscience, 2025)
Parkinson’s disease (PD) is a complex neurodegenerative disorder characterized by a pathology that includes the aggregation of alpha-synuclein (α-syn), oxidative stress, and neuroinflammation. While existing treatments can alleviate motor symptoms, they have limited efficacy in slowing disease progression and improving non-motor symptoms. In recent years, molecular hydrogen has been recognized for its potential neuroprotective effects, attributed to its selective antioxidant and anti-inflammatory properties. While preclinical studies demonstrate promising results, clinical trials conducted thus far have yielded mixed outcomes, with some trials reporting limited or no therapeutic benefit. This review systematically analyzes the mechanisms of action of molecular hydrogen in PD and related neurodegenerative disorders, emphasizing its antioxidant, anti-inflammatory, and anti-apoptotic properties. By evaluating evidence from both preclinical and clinical studies, this paper explores the potential of molecular hydrogen to attenuate oxidative stress, modulate inflammatory responses, and inhibit apoptosis in neuronal cells, while also identifying key gaps in current research. As a novel neuroprotective agent, molecular hydrogen holds potential in PD and other neurodegenerative diseases, but further well-designed clinical trials are needed to validate its efficacy. Future studies should focus on elucidating the mechanisms through which hydrogen exerts its neuroprotective effects, particularly concerning α-syn aggregation and its clearance pathways, as well as Nrf2-mediated immunomodulation. Furthermore, large-scale, multicenter clinical trials are necessary to establish efficacy benchmarks and personalized delivery protocols.